Shooting 'sublime blondes in tight dresses': the paparazzi in fiction film and television from La dolce vita to Dirt. Issue 1 (2nd January 2016) - Fossard De Almeida, Aurore
Abstract : In his 1960 film La dolce vita, Italian filmmaker Federico Fellini called his photographer 'Paparazzo'. Although photographers who snap celebrities, with or without consent, and sell the results to the press existed before La dolce vita, Fellini's nickname for them endured. The figure of the paparazzo has, from that moment, served as a convenient tool for a number of filmmakers to observe, get close to, and unveil their favourite subject: the blond bombshell – as illustrated by Sylvia (Anita Ekberg) in La dolce vita, Jill (Brigitte Bardot) in Vie privée/A Very Private Affair and Stormy (Stormy Daniels) in the television series Dirt . Using Visual Studies methodology, this article analyses what is at stake when representing the male photographer's perspective as he captures the blonde woman in his viewfinder. This article argues that the film director uses the paparazzo as an agent of visibility and discovery to unveil the female character, to glorify her, but also to degrade her.